Applications of water activated by ozone, electrolysis, or gas plasma for microbial decontamination of raw and processed meat - Roobab, Ume; Madni, Ghulam Muhammad; Ranjha, Muhammad Modassar Ali Nawaz; Khan, Abdul Waheed; Selim, Samy; Almuhayawi, Mohammed S.; Samy, Mennatalla; Zeng, Xin-An; Aadil, Rana Muhammad (Frontiers in Sustainable Food Systems, 2023)
A raw or processed meat product can be a breeding ground for spoilage bacteria (Enterobacteriaceae, Lactobacillus spp., Pseudomonas spp., etc.). Failure of decontamination results in food quality loss and foodborne illnesses caused by pathogens such as Salmonella, Escherichia coli, Staphylococcus aureus, and Listeria monocytogenes. Often, meat processors decontaminate the carcass using cheap chemicals or artificial antimicrobial agents not listed on the ingredient list, which is discouraged by health-conscious consumers. Foods with clean labels became more popular during the COVID-19 pandemic, which led consumers to choose healthier ingredients. Novel methods of controlling or improving meat safety are constantly being discovered. This review focuses on novel means of electrochemically activate water that is being investigated as a sanitizing agent for carcasses and processing area decontamination during production or at the end. Water can be activated by using nonthermal techniques such as ozonation, electrolysis, and cold plasma technologies. Recent studies showed that these activated liquids are powerful tools for reducing microbial activity in raw and processed meat. For instance, plasma-activated water can be used to enhance microbiological safety and avoid the negative effects of direct gaseous plasma on the organoleptic aspects of food products. In addition, electrolyzed water technology offers hurdle enhancement by combining with nonthermal strategies that have great potential. Ozonation is another way of activating water which provides a very convenient way to control microbiological safety and finds several recent applications as aqueous ozone for meat decontamination. These solutions are highly reactive and convenient for non-conventional applications in the meat industry related to food safety because of their antimicrobial or antiviral impact. The present review highlights the efficacy of activated-water decontamination of raw and processed meat via nonthermal solutions.